AB0657 IMPROVEMENT IN DISEASE ACTIVITY IS ASSOCIATED WITH ENHANCEMENT IN THE QUALITY OF LIFE DURING TUMOUR NECROSIS ALPHA INHIBITOR TREATMENT; A PROSPECTIVE COHORT EXPERIENCE IN AXIAL SpA. (2nd June 2020) - Otman Akat, E.; Solmaz, D.; Durak Ediboglu, E.; Kabadayi, G.; Oz, H. E.; Cinakli, H.; Kurut Aysin, İ. and Gucenmez, S. and Bayindir, O. and Ozmen, M. and Akar, S.
Abstract : Background: Axial spondyloarthritis (axSpA) is a chronic inflammatory condition affecting mainly axial skeleton. The disease usually starts in early adulthood and cause considerable impact on physical function, work ability and quality of life (QoL). With the introduction of tumour necrosis factor inhibitors (TNFi) significant improvement in articular and extra-articular manifestations of disease was shown in randomized controlled trials and several registries. However, there is limited data about the effects of TNFi therapy on QoL and the relationship between inflammation and QoL in cohort studies before. Objectives: To evaluate the influence of TNFi agents on different aspects of QoL which might be a significant determinant of patient burden in axSpA patients in parallel with disease activity. Methods: In total 83 TNFi naïve axSpA patients (62.7% male; mean age 40.6 ± 12 years) according to the ASAS criteria were included in this prospective observational cohort study between 2014-2018. Demographic and disease related characteristics were collected at baseline. Disease activity (BASDAI, ASDAS-CRP), function (BASFI) and QoL (SF-36 and ASQoL) were evaluated at baseline and 24 th and 52 nd weeks of follow-up. The changes in disease activity, function and QoL were assessed with Wilcoxon test and relationship between changes in QoL and activity on week 24 was evaluated by Spearman's correlation analysis. Results: Baseline disease related characteristics, disease activity and QoL scores were presented in table 1. Both disease activity and QoL were significantly improved at 24 th and 52 th weeks (Figure 1). The change of SF-36 subscales and summary scores at weeks 24 were correlated with the change in disease activity and function (Table 2). The SF-36 scale and summary scores were found to be similar at 24 and 52 weeks of TNFi treatment (Figure 2). Conclusion: The results of the present study suggest that TNFi treatment have a substantial influence on QoL in parallel to the control of disease activity at 24 th weeks of treatment and this effect was sustained at 52 weeks not only randomized controlled trials but also real life experience. Disclosure of Interests: None declared